Comparison of point-of-care glucometers and laboratory based glucose oxidase test in determining blood glucose levels - Babatunde Oluwatosin Ogunbosi; Olatokunbo Olumide Jarrett; Adebola Emmanuel Orimadegun; Omolola Oluwakemi Ayoola; Kike Osinusi (Nigerian Journal of Paediatrics, 2024)
Introduction: Alterations in blood glucose levels are common and an important determinant of a patient's admission outcomes, point-of-care glucometers, which are affected by a variety of factors, are increasingly used in clinical care. In this study we compared blood glucose levels determined by two commonly used glucometers (One Touch® and Accu-check® ) with those of a standard laboratory method and determined the effect of haematocrit on glucose readings Methods: Blood glucose levels were measured with One Touch® and Accu-Check® glucometers and the glucose oxidase method at the same time in 295 children aged 0 to 15 years over a 6-month period. Bland-Altman and correlation analysis were used to explore biases among the three methods. For all statistical tests, a p-value of less than 0.05 was considered statistically significant. Results: Most were males (51.2%) and the median (range) age was 1 year (1 day, 12 years). There was a significant correlation between each of the glucometer methods and laboratory blood sugar, and the correlation between the two glucometers was strong and significant. This correlation remained statistically significant even after controlling for haematocrit values. There was an acceptable level of bias (3.9 mg/dL) between the One Touch® and Accu-check® glucometers, but each had a remarkably large bias compared with the glucose oxidase method. Conclusion: The use of a tested glucometer in clinical settings can aid in rapid decision-making, but there is a need to periodically cross -check with the glucose oxidase method in the laboratory to optimise treatment outcomes for children with dysglycaemia.